Successful Outcome of Post Liposuction Extensive Necrotizing Soft Tissue Infection of Abdomen and Concomitant Jejunal Perforation—A Case Report - Hardeep Singh; Rakesh Kumar Khazanchi; Sanjay Mahendru (Indian Journal of Plastic Surgery, 2019)
Introduction Liposuction is one of the common cosmetic surgery procedures performed. Although rare, the complications associated with it are necrotizing soft tissue infection and bowel perforation. We would like to share our experience of such a complication that was managed successfully. Case Report We were referred a 65-year-old male patient with signs and symptoms of intestinal obstruction who had undergone liposuction of abdomen 1 week before and now had discoloration of the abdominal skin. The discoloration was present from just below the costal margin and was extending up to bilateral inguinal regions. Laterally the discoloration extended up to the mid axillary line on both sides. Imaging studies showed dilated small bowel. During laparotomy, he underwent debridement of all discolored skin and repair of the single jejunal perforation. Postoperatively patient was first managed on intravenous fluids, nasogastric aspiration and total parenteral nutrition for 10 days. The wound was managed with silver dressings that led to healthy granulations. The patient was at high risk for anesthesia for skin grafting; hence, he was managed with allograft for 10 days. The patient then underwent skin grafting once he was fit. The graft took up well and he resumed regular activities. Conclusion This is unique as the patient had extensive necrotizing soft tissue infection of the abdominal skin after liposuction along with intestinal perforation and obstruction that was managed successfully due to aggressive surgical intervention, allograft, and good supportive care both in the intensive care unit and in ward.